REFORMASI BIROKRASI ORGANISASI PEMERINTAHAN DALAM UPAYA PERBAIKAN PELAYANAN TRANSPORTASI PUBLIK (STUDI KASUS PENGELOLAAN TERMINAL MANGKANG) - Irvan Mardiansyah .; Teguh Yuwono .; Dzunuwanus Ghulam Manar (Journal of Politic and Government Studies, 2017)
BUREAUCRATIC REFORM OF ORGANIZATION IN AN EFFORT TO IMPROVE PUBLIC TRANSPORT SERVICES (CASE STUDIES IN TERMINAL MANGKANG MANAGEMENT)ABSTRACTBureaucratic reform is essentially an effort changes made consciously, to position themselves (bureaucracy) is back, in order to adapt to a dynamic environment dynamics, as well as to improve the performance of the bureaucracy in providing service to the community. The Terminal is the terminal type Mangkang that exists in the city of Semarang and managed by Dishunkominfo Semarang. As a public facility, the terminal should be able to provide a service to the community with the best. However, since the terminal mangkang operated until this time the terminal was still not functioning with optimal in providing service to the community, therefore Dishubkominfo considered the need for reform in UPTD Terminal Mangkang as terminal Manager mangkang in order to improve its performance in managing mangkang terminal in order to provide good service to the community.The purpose of this study is to find anything bureaucracy reform of government especially the uptd terminal mangkang as the management of mangkang terminal . A method of research used is research methodology qualitative. The research was done at the uptd terminal mangkang and terminal mangkang. Instrument research by interviews, observation and study documentation was done with certain sources.The result of this research indicates that there are some effort of reforms, reform efforts done by means of change the organizational structure, change behaviors and habits of employees and providing education and training. The obstacles faced by in reform efforts are poor quality of human resources and lack of budget for education and training.Advice provided to Dishubkominfo Kota Semarang is need of study and research deep relating to the effectiveness of management systems mangkang terminal, there should have been study thoroughly related potential mangkang terminal, there should have been good coordination with other parties in optimizing terminal mangkang, improvement facilities terminal , and perform various innovations such as smartcard , barcode door , and the installation of cctv in the station .Keywords: bureaucratic reform , public transport services , mangkang terminal.